John Sumner interviewed by Hazel de Berg for the Hazel de Berg collection - Sumner, John, 1924-2013.; De Berg, Hazel, 1913-1984. (1971)
Sumner speaks of his school life; the effects of the war on him; the beginning of his professional life in theatre (1947); moving into the film industry; various actors he has worked with; his career in Australia; producing Australian plays; the formation of the Union Theatre Repertory Company; directing plays.
Digital master available
Transcript available (27 p.)
Keywords: Sumner, John, -- 1924-2013 -- Interviews; Theatrical producers and directors -- Australia -- Interviews